Identificación y estabilización de las antocianinas por acoplamiento con magnesio de dioscorea trifida L. para su uso en alimentos 2023 - Gallardo Dahua, Severino (2024)
Dioscorea trifida L. (Sachapapa morada) is a plant of the Dioscoreaceae family of wild origin and used in food by the native groups that have populated the Amazon for centuries. The objective of the present work was to extract the dye matrix and stabilize it by derivatization through the formation of a coordination complex using magnesium oxide and HCl. The sample was collected in the town of Nuevo Oriente, Mazan District, Maynas Province, Loreto Region. The tuber was grated to reduce it to small particles. To extract the matrix dye, methanol acidified with hydrochloric acid was used to bring it to an acid medium. Identification of the matrix dye components was by paper chromatography, using concentrated hydrochloric acid - acetic acid - water and concentrated hydrochloric acid - formic acid - water as solvents for resolution. The anthocyanidins identified were: cyanidin, peonidin, malvidin, and pelargonidin, and their respective anthocyanins were: cyanidin-3-rhamnosyl-glucoside, peonidin-3,5-diglucoside, malvidin-3,5- diglucoside and pelargonidin-3,5-diglucoside. The stabilization of the anthocyanins was achieved by reduction of the flavilium ion upon formation of the hexacoordinate coordination complex of an octahedral geometric structure named [η6(anthocyanin)6Magnesium II].6Cl- at pH 3.5 of intense blue color. It obtained 2.086g of stabilized dye, constituting a new method of stabilization of natural dyes that will serve in future investigations to determine its degree of toxicity and to make possible its use in the natural dyes industry.